Naturvägledning i Isidro Fabela, Mexico - Hammar, Louise (2016)
The increasing degree of urbanization among world’s population leads to the situation that majority of people do not have much contact with nature. This contact seems to be however quite important. The nature interpretation is a way to enhance this contact and also to make it more attractive. In this study, I analyzed a partially protected landscape in Isidro Fabela in vicinity of Mexico City in order to propose nature interpretation trails that would enable inhabitants of this megacity opportunity to experience and learn about nature. Three different trails were initially planned and assessed using both semi-quantitative and qualitative approaches. Later, the most attractive trail has been designed more in detail. Finally, I discuss my approach in broader perspective and contrast prerequisites for nature interpretation in developing and developed countries.